Porphyromonas gingivalis Provokes Exosome Secretion and Paracrine Immune Senescence in Bystander Dendritic Cells - Elsayed, Ranya; Elashiry, Mahmoud; Liu, Yutao; El-Awady, Ahmed; Hamrick, Mark; Cutler, Christopher W. (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic periodontitis is a disease of ageing or inflammaging, and is comorbid with other more severe age-related chronic diseases. With advanced age comes an increase in accumulation of senescent cells that release soluble and insoluble pro-inflammatory factors collectively termed the senescence associated secretory phenotype (SASP). In the present report, we examined whether immune and non-immune cells typical of those at the oral mucosa-microbe interface, are vulnerable to cellular senescence (CS) and the role of dysbiotic oral pathogen Porphyromonas gingivalis. Human primary isolated gingival keratinocytes (HPGK) and bone marrow-derived dendritic cells (DCs) from young (yDCs) and old (oDCs) mice were co-cultured in vitro with CS inducer doxorubicin or P.gingivalis (Pg), plus or minus senolytic agent rapamycin. CS profiling revealed elevated CS mediators SA--Gal, p16 INK4A, p53, and p21Waf1/Clip1 in HPGK and oDCs, or yDCs in response to doxorubicin or P. gingivalis, reversible with rapamycin. Functional studies indicate impaired maturation function of oDCs, and yDC exposed to P. gingivalis; moreover, OVA-driven proliferation of CD4+ T cells from young OTII transgenic mice was impaired by oDCs or yDCs+Pg. The SASP of DCs, consisting of secreted exosomes and inflammasome-related cytokines was further analyzed. Exosomes of DCs cocultured with P. gingivalis (PgDCexo) were purified, quantitated and characterized. Though typical in terms of size, shape and phenotype, PgDCexo were 2-fold greater in number than control DCs, with several important distinctions. Namely, PgDCexo were enriched in age-related miRNAs (miR132-3p), and miRNAs reported to disrupt immune homeostasis through negative regulation of apoptosis and autophagy functions, such as miR106b, miR-17-5p, miR378a-3p, miR-324-5p, miR-132-3p, and miR17-5p. We further show that PgDCexo were enriched in P. gingivalis fimbrial adhesin protein mfa1 and in inflammasome related cytokines IL-1, TNF and IL-6. Functionally PgDCexo were readily endocytosed by recipient yDCs, shutting down maturation functions and rendering yDCs unable to promote Ova-driven proliferation of OTII CD4+ T cells from young mice. In conclusion P. gingivalis induces premature senescence through direct cellular invasion and by stimulating secretion of inflammatory exosomes that promote paracrine immune senescence in bystander cells. The implications of this pathological pathway for periodontal disease in vivo is under investigation in mouse models.